Patient's dissatisfaction with the public and private laboratory services in conducting HIV related testing in Tanzania - Mtandu R; Ngowi B; Senkoro M; Kivuyo S; Kilale A; Kimaro G; Kahwa A; Mfinanga SG; Mutayoba B; Ngadaya E; Mashoto K (BMC, 2008)
Abstract Background Patient's satisfaction with both private and public laboratory services is important for the improvement of the health care delivery in any country. Methods A cross-sectional survey was conducted in 24 randomly selected health facilities with laboratories that are conducting HIV related testing, in Mainland Tanzania. The study assessed patient's satisfaction with the laboratory services where by a total of 295 patients were interviewed. Results Of data analyzed for a varying totals from 224 to 294 patients, the percentage of dissatisfaction with both public and private laboratory services, ranged from 4.3% to 34.8%, with most of variables being more than 15%. Patients who sought private laboratory services were less dissatisfied with the cleanness (3/72, 4.2%) and the privacy (10/72, 13.9%) than those sought public laboratory service for the same services of cleanness (41/222, 18.5%) and privacy (61/222, 27.5%), and proportional differences were statistically significant (X2 = 8.7, p = 0.003 and X2 = 5.5, p = 0.01, respectively). Patients with higher education were more likely to be dissatisfied with privacy (OR = 1.8, 95% CI: 1.1-3.1) and waiting time (OR = 2.5, 95% CI: 1.5 - 4.2) in both private and public facilities. Patients with secondary education were more likely to be dissatisfied with the waiting time (OR = 5.2; 95%CI: 2.2-12.2) and result notification (OR = 5.1 95%CI (2.2-12.2) than those with lower education. Conclusion About 15.0% to 34.8% of patients were not satisfied with waiting time, privacy, results notification cleanness and timely instructions. Patients visited private facilities were less dissatisfied with cleanness and privacy of laboratory services than those visited public facilities. Patients with higher education were more likely to be dissatisfied with privacy and waiting time in both private and public facilities.